(untitled) (Sciences & Technology. A, exactes sciences, 2007)
The aim of this study was the determination of the thermal expansion coefficient α (T) in relation to the temperature of the three following aluminium alloys: - Al-6%Zn-3%Mg obtained by conventional ingot casting - Al-0.5%Mg-0.88%Si obtained by Direct Cast Casting - Al-1.88%Mn-0.8%Mg obtained by Twin Roller Melt Spinning These alloys have undergone various thermal and mechanical conditions. The main results show that the Al-6%Zn-3%Mg alloy exhibits a very weak anisotropy meanwhile that Al-Mg-Si and Al-Mn-Mg alloys exhibit, on the contrary, a quite strong anisotropy on the curves of α (T).